# Formulario Trigonométrico

 1 cosec  = 1 _____ sen  RECIPROCIDAD 2 sec  = 1 _____ cos  3 ctg  = 1 _____ tg  4 tg  = sen  _____ cos  RELACIÓN tg/ctg 5 ctg  = cos  _____ sen  6 sen2 + cos2 = 1 PITAGÓRICAS 7 1 + tg2 = sec2 8 1 + ctg2 = cosec2 9 sen ( + ) = sen  · cos  + cos  · sen  ADICIÓN 10 cos ( + ) = cos  · cos  - sen  · sen  11 tg ( + ) = tg  + tg  _______ 1 - tg  · tg  12 sen ( - ) = sen  · cos - cos  · sen  13 cos ( - ) = cos  · cos  + sen  · sen  14 tg ( + ) = tg  + tg  _______ 1 - tg  · tg  15 sen (2) = 2 sen  · cos  ÁNGULO DOBLE 16 cos (2) = cos2 - sen2 17 tg (2) = 2 tg  _______ 1 - tg2 18 sen2 = 1 - cos (2) _______ 2 ÚTILES PARA INTEGRAR 19 cos2 = 1 + cos (2) _______ 2 20 sen2 /2 = 1 - cos  _______ 2 ÁNGULO MITAD 21 cos2 /2 = 1 + cos  _______ 2 22 tg2 /2 = 1 - cos  _______ 1 + cos 

 23. A + B A - B DE SUMAS A PRODUCTOS sen A + sen B = 2 sen ___ · cos ___ 2 2 24. A + B A - B sen A - sen B = 2 cos ___ · sen ___ 2 2 25. A + B A - B cos A + cos B = 2 cos ___ · cos ___ 2 2 26. A + B A - B cos A - cos B = -2 sen ___ · sen ___ 2 2

 1 cosec  = 1 _____ sen  RECIPROCIDAD 2 sec  = 1 _____ cos  3 ctg  = 1 _____ tg  4 tg  = sen  _____ cos  RELACIÓN tg/ctg 5 ctg  = cos  _____ sen  6 sen2 + cos2 = 1 PITAGÓRICAS 7 1 + tg2 = sec2 8 1 + ctg2 = cosec2 9 sen ( + ) = sen  · cos  + cos  · sen  ADICIÓN 10 cos ( + ) = cos  · cos  - sen  · sen  11 tg ( + ) = tg  + tg  _______ 1 - tg  · tg  12 sen ( - ) = sen  · cos - cos  · sen  13 cos ( - ) = cos  · cos  + sen  · sen  14 tg ( + ) = tg  + tg  _______ 1 - tg  · tg  15 sen (2) = 2 sen  · cos  ÁNGULO DOBLE 16 cos (2) = cos2 - sen2 17 tg (2) = 2 tg  _______ 1 - tg2 18 sen2 = 1 - cos (2) _______ 2 ÚTILES PARA INTEGRAR 19 cos2 = 1 + cos (2) _______ 2 20 sen2 /2 = 1 - cos  _______ 2 ÁNGULO MITAD 21 cos2 /2 = 1 + cos  _______ 2 22 tg2 /2 = 1 - cos  _______ 1 + cos 

 23. A + B A - B DE SUMAS A PRODUCTOS sen A + sen B = 2 sen ___ · cos ___ 2 2 24. A + B A - B sen A - sen B = 2 cos ___ · sen ___ 2 2 25. A + B A - B cos A + cos B = 2 cos ___ · cos ___ 2 2 26. A + B A - B cos A - cos B = -2 sen ___ · sen ___ 2 2

 Enviado por: Julia Fontana Idioma: castellano País: España

Palabras clave:
Te va a interesar